Resource Leveling Based on Line of Balance and Constraint Programming. (30th June 2018) - Tang, Yuanjie; Sun, Quanxin; Liu, Rengkui; Wang, Futian
Abstract: This study investigated resource leveling problems concerning linear construction projects based on the line of balance (LOB) technique and constraint programming. In addition, an LOB‐based scheduling optimization model for resource leveling is proposed. This model retains the advantages of the conventional models, including multiple‐resource management and natural rhythm concept, and showcases new abilities: scheduling optimization without specifying a fixed schedule; scheduling optimization on more comprehensive optimization objects and variable values; maintaining continuity of resource while completely eliminating the occurrence of idle time; handling more comprehensive constraints after the addition of logical constraints and explicit expression of certain new constraints. The flexibility, practicality, and solution quality of the proposed model were enhanced accordingly. Further, a scheduling system was developed to assist in schedule optimization and visualization. Lastly, effectiveness of the proposed model was verified based on four case studies involving three case projects investigated in extant LOB‐based studies.